(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The study was aimed at finding out the changes occurred in different aspects of socioeconomic conditions of the framers due to adoption of rice production technologies. For the present study data were collected from 90 randomly selected farmers in three villages of Gourdwer union under Nakla upazila of Sherpur district with the help of interview schedule. Correlation and t-test were used to ascertain the relationship between the concerned dependent and independent variables. Findings revealed that about 51 percent of the farmers had medium adoption while 33 percent had high adoption of rice production technologies. Correlation analysis indicates that education, annual income showed significant positive relationships, and age and family size of the farmers showed significant negative relationships with their adoption of rice production technologies. Besides farm size did not show any significant relationship with their adoption. Findings also showed a significant increase in annual income (from Tk.88.82 thousand to Tk.109.26 thousand), food consumption expenditure (from Tk.17.35 thousand to Tk.20.41 thousand), housing environment (scores rose to 14.22 from 7.82) and family status of the framers (scores increased from 19.46 to 27.82). The differences between before and after changes in income, expenditure, housing environment score and family status score were statistically significant. Keywords: Rice production technology; Adoption; Socioeconomic changes DOI: 10.3329/jbau.v7i2.4744 J. Bangladesh Agril. Univ. 7(2): 335-341, 2009